2007
DOI: 10.1007/s00535-006-1984-x
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of universal vaccination of children against hepatitis A in Argentina: results of a dynamic health–economic analysis

Abstract: Routine childhood vaccination against hepatitis A showed both health benefits and robust economic benefits in this analysis, supporting the recent decision of the Argentine government to implement such a program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
1
44
1
2
Order By: Relevance
“…8 In the context of health economic perspective, however, the implementation of the one-dose vaccine schedule would be more realistic to be implemented in Indonesia. Related to the sensitivity analyses, the results in this study reconfirmed the results from several previous studies that the vaccine price, [18][19][20] mortality rate, 21 and discount rate, 14,18,22,23 were the most influential parameters impacting the ICERs in the implementation of hepatitis A vaccination. However, the dominant role of the vaccine price might lead the small difference between the ICERs from the healthcare and societal perspectives.…”
Section: Discussionsupporting
confidence: 85%
“…8 In the context of health economic perspective, however, the implementation of the one-dose vaccine schedule would be more realistic to be implemented in Indonesia. Related to the sensitivity analyses, the results in this study reconfirmed the results from several previous studies that the vaccine price, [18][19][20] mortality rate, 21 and discount rate, 14,18,22,23 were the most influential parameters impacting the ICERs in the implementation of hepatitis A vaccination. However, the dominant role of the vaccine price might lead the small difference between the ICERs from the healthcare and societal perspectives.…”
Section: Discussionsupporting
confidence: 85%
“…Economic model assessments in some developed and developing countries showed that widespread childhood vaccination could be cost-effective, [36][37][38] and immunization programs in several populations have significantly reduced hepatitis A rates. In 2008, an analysis using the Markov model was performed to evaluate whether universal childhood hepatitis A vaccination is advisable now in China.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Previous studies have shown that HAV infection in adulthood is symptomatic in 75% to 90% of cases, and case fatality rates exceed 2.1% among those aged 40 y or older. 50,51 Thus, although levels of endemicity fall, hepatitis A can impose a serious healthcare and economic burden. Strategies for catch-up immunization may be considered as components of universal immunization programs.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Methodological characteristics of the studies Table 1 shows the methodological characteristics of the 10 studies 20,21,22,23,24,25,26,27,28,29 analyzed in the current review. Half of the studies were conducted in developed countries, the oldest 20 failed to specify the country but used U.S. data in its analysis, three studies were performed in the United States 21,22,23 , and one in Israel 24 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Half of the studies were conducted in developed countries, the oldest 20 failed to specify the country but used U.S. data in its analysis, three studies were performed in the United States 21,22,23 , and one in Israel 24 . Four studies were conducted in South America, including two in Chile 25,26 and two in Argentina 27,28 , and one study in China 29 .…”
Section: Literature Reviewmentioning
confidence: 99%